THEORETICAL ASPECTS OF SEPARATE (UNITARY) CRIMINAL OFFENCES - Krastiņš, Uldis (Administrative and Criminal Justice, 2017)
The article analyses the aspects of the understanding of separate (unitary) criminal offense. Under Section 23 of the Criminal Law, separate (unitary) criminal offenses can be subdivided into simple and complex unitary criminal offenses. Particular attention is paid to the analysis of complex criminal offenses, such as constituent criminal offenses, continuous and continuing criminal offences. The criteria for the delimitation of complex offenses from conceptual aggregation and factual aggregation of criminal offenses are also considered.